IMT to Satellite Stochastic Interference Modeling and Coexistence Analysis of Upper 6 GHz-Band Service - Reza Aghazadeh Ayoubi; Dario Tagliaferri; Filippo Morandi; Luca Rinaldi; Laura Resteghini; Christian Mazzucco; Umberto Spagnolini (IEEE Open Journal of the Communications Society)
The surging capacity demands of 5G networks and the limited coverage distance of high frequencies like millimeter-wave (mmW) and sub-terahertz (THz) bands have led to consider the upper 6 GHz (U6G) spectrum for radio access. However, due to the presence of the existing satellite (SAT) services in these bands, it is crucial to evaluate the impact of the interference of terrestrial U6G stations to SAT systems. A comprehensive study on the aggregated U6G-to-SAT interference is still missing in the literature. In this paper, we propose a stochastic model of interference (SMI) to evaluate the U6G-to-SAT interference, including the statistical characterization of array gain and clutter-loss and considering different interference modes. Furthermore, we propose an approximate geometrical-based stochastic model of interference (GSMI) as an alternative method to SMI when the clutter-loss distribution is unavailable. Our results indicate that given the typical international mobile telecommunication (IMT) parameters, the aggregated interference power toward the geostationary (GEO) SATs, is well below the relevant protection criterion, and we prove numerically that the GSMI method overestimates the aggregated interference power with only 2 dB compared to the SMI method.